THE CONCEPT OF THE QUALIFICATIONS FRAMEWORK IN THE SPHERE OF INFORMATION TECHNOLOGIES - E. Vasilyeva (Финансы: теория и практика)
The qualifications framework is an important element of the qualification certification system. It is a compromise between the labor market requirements for qualifications and the academic learning outputs in a specific professional line. The structure of the IT qualifications framework is based on the European framework approach to the skill levels division and the requirements of employers in the IT sector declared in professional standards of the Information and Computer Technologies Industry Association («APKIT» in Russian). The article proposes IT qualifications framework descriptors and describes selection criteria for qualification, knowledge, skill and competency levels. The consistency of job titles and learning outcomes is determined. The specific feature of the IT qualifications framework is that the levels established by it include not only the existing educational levels (bachelor, specialist, master, graduate and doctoral degrees - levels 1, 2, 4, 6, 8, but also additional skill levels reflecting professional experience and additional vocational education in the MBA and EMBA systems, certification centers, informal training - qualification levels 3,5,7 and 9. The research was carried out under the INARM (Informatics and Management: Bologna Style Qualifications Frameworks) project of the European Union TEMPUS program.